ANALYTICAL - PROGNOSTIC MODEL OF THE TECHNIQUE OPERATION (Advances in Military Technology, 2022)
The article introduces a dynamical model of the technique's operation (generally). The model enables to describe reciprocal structures of basic operational phenomena, analyse progress tendencies of operational coefficients and determine prognosis of a future progress of the technique's operation.